(3JfhjQ GdacQI HMOjK HgR Hf Mcje aj MSf GdYTQIs - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GNHQfG GdTjN GdeSfO GdUGdM GdebQi CHh GSMGb GHQGgje Hf eMeO Hf UOjb Hf GHQGgje Hf jhSa GdUhai GdeLGhQ bQGAI hCfG CSeY HLGeY OeTb s
(3BNQgG (B:s
(3hYdi GdUMGH hBdg hCfGdg TQa GdhSjdI ai MXjQI bOSg BNQ GdeLdS GdeSei JfhjQ GdacQI HMOjK HgP Hf Mcje ai MSf GdYTQI s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW Cged ajg GdfbW CMjGfkG fbdkG Yf fSNI HNW GdeDda hYdi MGTjI fSNJfG gPg SeGY HNW GdeDdas
(3hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN hTgO GdeDda Ydi UMI gPG HNWg hUaMI GdZdGa GjVkG HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs